Analysis of the Use of Language Style in Poetry by Grade X Students of SMA Negeri 10 Padang - Desfebriani; Al Khansa Humaira Fadil; Adinda Resky Utami; Huriyah Husna; Rizky Khoirunnisa Siregar; Afnita (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Poetry is a medium of literary expression rich in the use of language styles and reflects students' creativity, imagination, and cultural experiences. This study aims to describe the types and characteristics of language styles used in poetry by tenth-grade high school students in Padang, identify the most dominant language styles, and reveal their implications for literature learning in secondary schools. This study uses a qualitative descriptive method with data sources in the form of 36 student poems with the theme of natural beauty, especially Lake Toba. The data collection instrument used was a performance test in the form of a poetry writing assignment, equipped with a language style analysis guide sheet based on Keraf and Tarigan's theory. After the data were collected, the poems were analyzed through the stages of classifying language style types, calculating the frequency of occurrence, and interpreting language style characteristics contextually. The results showed that metaphor and personification were the most dominant styles. Both styles have imaginative, concrete, and emotional characteristics, which reflect students' tendency to concretize natural experiences into poetic expressions. In addition, simile, repetition, and hyperbole were also found with the characteristics of emphasizing meaning and strengthening emotional expression. The dominance of these styles of language indicates that students are at a stage of literacy development that still relies on sensory experience and local cultural influences to express ideas. This finding implies the importance of more contextual poetry learning, oriented toward enriching the variety and characteristics of language styles, so that students' literary appreciation and creativity can develop optimally.